Multislice CT Angiography of Fenestrated Endovascular Stent Grafting for Treating Abdominal Aortic Aneurysms: a Pictorial Review of the 2D/3D Visualizations - Sun, Zhonghua; Mwipatayi, B.; Allen, Yvonne; Hartley, D.; Lawrence-Brown, Michael (Korean Radiological Society, 2009)
Fenestrated endovascular repair of abdominal aortic aneurysm has been developed to treat patients with short or complicated aneurysm necks. Fenestration involves creating an opening in the graft fabric to accommodate the orifice of the vessel targeted for preservation. Fixation of the fenestration to the renal and other visceral arteries can be provided by implantation of bare or covered stents across the graft-artery ostia interfaces so that a portion of the stents protrudes into the aortic lumen. Accurate alignment of targeted vessels in a longitudinal aspect is hard to achieve during deployment because rotation of stent graft may take place during delivery from the sheath. Understanding the 3D relationship of aortic branches and fenestrated vessel stents following fenestration will aid endovascular specialists to evaluate how the stent grafts situate within the aorta after placement of fenestrations. The aim of this article is to provide 2D and 3D imaging appearances of fenestrated endovascular grafts which were implanted in a group of patiens with abdominal aortic aneurysms, based on multislice CT angiography. Potential applications of each visualization technique were explored when compared to 2D axial images.